Comparative Analysis of the Influence of Verbal and Nonverbal Reprimands in Enforcing Discipline of Grade VI Students - Lalu Dodi Suwandi; Abdul Hayyi Akrom (EDUJAVARE: International Journal of Educational Research, 2026)
Financial Performance represents the achievement of an entity's overall operational activities measured through financial indicators within a specific period. This research aims to comparatively analyze the effect of verbal and nonverbal reprimands on enforcing student discipline in Grade VI at SDN 6 Masbagik Selatan. Employing a quantitative associative and comparative approach, this study involved a sample of 35 students selected through simple random sampling. Data were collected via questionnaires using a 4-point Likert scale, observation, and documentation. The data analysis included validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that verbal reprimands have a positive and significant effect on student discipline (t-count = 3.218 > t-table = 2.037), as explicit verbal communication provides clear stimuli for behavior correction. Conversely, nonverbal reprimands do not significantly affect discipline (t-count = -1.084 < t-table = 2.037), largely due to elementary students' limitations in interpreting symbolic or implicit gestures. Simultaneously, both variables account for a 52.5% variance in student discipline. The study concludes that educators should prioritize constructive verbal reprimands while utilizing nonverbal cues only assupplementary reinforcements to effectively foster student discipline.